Analisis kemampuan Lahan Kawasan Perkotaan Wawo Kabupaten Kolaka Utara - Rusneni Ruslan; Fachmi Anugroh Yahya; Batara Surya (Journal of Urban Planning Studies, 2021)
The purpose of this study is to find out what are the classifications of land capability in urban areas in Wawo District, North Kolaka Regency and to identify the land capability of urban areas in Wawo District, North Kolaka Regency. This study uses quantitative research methods as the main method and is supported by a spatial analysis approach. The analysis used in this study is to use overlay spatial analysis and descriptive analysis. The results of the spatial overlay analysis depend on the basic physical aspect data to determine the land capability classification, while the descriptive analysis is highly dependent on the results of the first analysis. The main conclusion of this research is that there are four (4) Class E with High Development Classification, Class D with Moderate Development Classification, Class C with Medium Development Classification, and Class D with Less Development Classification. Whereas the Land Capability for Development is Sufficient and High, it is very suitable to be used as land for development in urban areas and does not have physical environmental barriers, while the Capacity for Medium Development Land can still be developed into an urban area, and in areas with Less Development Land Capability it is not recommended to be used as a development area.